Development of baculovirus triple and quadruple expression vectors: co-expression of three or four bluetongue virus proteins and the synthesis of bluetongue virus-like particles in insect cells. - Belyaev, A S (1993)
Baculovirus multiple gene transfer vectors pAcAB3 and pAcAB4 have been developed to facilitate the insertion of three or four foreign genes respectively into the Autographa californica nuclear polyhedrosis virus (AcNPV) genome by a single co-transfection experiment. The pAcAB3 vector contains a polyhedrin promoter and two p10 promoters on either side of the polyhedrin promoter but in opposite orientations. The pAcAB4 vector has an additional polyhedrin promoter in opposite orientation to the first copy that is in juxtaposition to the first p10 promoter. Each of these derived vectors (pAcAB3, pAcAB4) have been used for the simultaneous expression of three or four bluetongue virus (BTV) genes respectively. When Spodoptera frugiperda cells were infected with the recombinant virus (AcBT-3/2/7/5) expressing the four major structural genes of BTV, double-capsid, virus-like particles consisting of VP2, VP3, VP5 and VP7 of BTV were assembled.